Understanding the 4th Market of Children as Consumers - Agusanto Mulyawan; Jehan Nabilah; Silvia Irawan; Jony Oktavian Haryanto (Budapest International Research and Critics University, 2022)
There are some aspects that can impact a consumer's purchase decision. Before purchasing a product or using a service, a consumer will examine a number of things. In addition to this study, there is an unconscious behaviour carried out by a consumer before making a decision. According to the previous studies, there is still a lack of research into children as a future market or the factors that impact parents' purchase decisions for their children. Twenty participants were subjected to a series of directed in-depth interviews, which were grouped by gender (male and female) and income (middle low and middle up). This research has been conducted between October 2021 and January 2022. Researchers discovered that the higher a parent's income is, the more thoughts they have before purchasing goods or services, and the higher a parent's educational level is, the more considerations they have before purchasing goods or services. Before purchasing products or services, parents think about their children's health, safety, comfort, and educational value of the goods or services.